PENGARUH PEMBELAJARAN BERBASIS KOMPUTER MODEL TUTORIAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA MUHAMADIYAH 1 PALEMBANG - Yuliana FH; Riswan Jaenudin; Deskoni Deskoni (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2015)
This study aims to determine the effect of computer-based tutorial learning model to the students’ learning outcomes on Economics subject at SMA Muhammadiyah 1 Palembang. The population occures in the class of X SMA Muhammadiyah 1 Palembang of the 2012-2013 school year, totaling 467 students. By using the random cluster sampling technique, it obtains as a class experiment, namely; Class X.4 given treatment in the form of PBK tutorial models and Class X.9 as a class controls a given treatment in the form of training and practice models CPB. This research is called “True Experimental Design, taking the form of posttest control design”. The data collection techniques uses validation sheets, observation sheets, and test. Data learning outcomes that have been obtained and analyzed using classical completeness KKM amounted 71dan ≥ 85%. To determine the effect of differences in the formula used t-test of two independent variables so obtained t of 4.9911> t table of 3.107. It was concluded that there are significant differences between computer-based learning tutorial models and models of training and practice on student learning outcomes.